x y = y x = x + y
If x , y = 0 satisfy the above equation. What is the value of x − y ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We've got x,y could not be 0 => xy=x/y <=> y=1/y => y= 1 or -1. If y=1 =>x=x+1 <=> 0=1 so y must be -1 => -x=x-1 <=> x=1/2 => x-y=1/2-(-1)=3/2=1.5
If xy=x/y, then x*y^2=x, therefore y^2=1.
Now, if x/y=x+y, then x=xy+y^2, so x=xy+1, and 1=y+1/x, therefore y=1-1/x.
Using that, we have that (1-1/x)^2=1, so 1+1/x^2 -2/x=1, and x^2+1-2x=x^2, therefore 2x=1, and x=1/2.
Operating that we have that y=1-2, so y=-1, and x-y=1/2-(-1)=3/2 or 1.5
x y = x/ y
=> y^2 = 1
=> y = +/- 1
With y = 1, x = x = x + 1 cannot be valid x.
With y = -1, - x = - x = x - 1 => x = 0.5
x - y = 0.5 - (-1) = 1.5
Given, xy= y x =x+y
Clearly, by Law of Transitivity, we have
xy=x+y
Which will give us,
x= y x + y
x= y x +1
Given that xy= y x
We get,
y= y x * x 1
y= y 1
We substitute this temporary value of y to x= y x +1
x= y x +1
x=x( y 1 )+1
x=xy+1
Notice that from xy=x+y, we get x=xy-y
With x=xy-y and x=xy+1, by the laws of transitivity, we have
xy-y=xy+1
-y=1
y= -1
We can now use the value of y to get the value of x.
Given, xy= y x =x+y
x(-1)= − 1 x =x+(-1)
-x=-x=x-1
or simply,
-x=x-1
-2x=-1
x= − 2 − 1
x= 2 1
Since y= -1 and x= 2 1 , therefore
x-y= 2 3 or 1.5
The solution is similar to Just a simple question #2 solution
Problem Loading...
Note Loading...
Set Loading...
From LHS: y = y 1 ⇒ y 2 = 1 ⇒ y = ± 1. Now if y = 1, then we have x = x = x +1, where the RHS results in 0=1, so by contradiction y = -1, ⇒ - x = x -1 ⇒ x = 2 1 .
∴ x - y = 2 3